STRATEGI KOMUNIKASI PEMASARAN FALABELLE DALAM BRANDING DI INSTAGRAM - Alfira Nurul Maulida, (2022)
Falabelle is a local beauty and skincare brand that was founded in 2019 with natural ingredients. In 2019 Falabelle had issued a product and was no longer in production, then in the next year Falabelle issued a new product with new packaging. With the increasing number of local skincare products available, Falabelle has to face business competition with competitors. To overcome this, a marketing communication strategy is needed with the aim of creating a strong brand so that it can attract and stick in the minds of consumers. This research was conducted using qualitative research methods, namely by using primary data from interviews and secondary data obtained from documentation and observation. The results of this study indicate that there is a match between the marketing communication strategy carried out by Falabelle and the integrated marketing communication theory, namely by applying five marketing tools in the form of advertising, sales promotion, personal selling, direct marketing and WoM, but in the application of the integrated marketing communication strategy carried out there are dominance of social media marketing used. Falabelle uses Instagram as an online promotion media to make it easier for customers to get information about Falabelle products. The strength of Falabelle branding as a supporting factor in carrying out marketing communication strategies in creating awareness and a good image from the community. Falabelle's branding is by using the tagline when nature meets technology #falabellebeauty, interacting with followers (followers), forming a skincare community and holding bundling and starterpack programs on Instagram.